Mycobacterium tuberculosis: Pathogenesis and therapeutic targets - Jiaxing Yang; Laiying Zhang; Wenliang Qiao; Youfu Luo (MedComm, 2023)
Abstract Tuberculosis (TB) remains a significant public health concern in the 21st century, especially due to drug resistance, coinfection with diseases like immunodeficiency syndrome (AIDS) and coronavirus disease 2019, and the lengthy and costly treatment protocols. In this review, we summarize the pathogenesis of TB infection, therapeutic targets, and corresponding modulators, including first‐line medications, current clinical trial drugs and molecules in preclinical assessment. Understanding the mechanisms of Mycobacterium tuberculosis (Mtb) infection and important biological targets can lead to innovative treatments. While most antitubercular agents target pathogen‐related processes, host‐directed therapy (HDT) modalities addressing immune defense, survival mechanisms, and immunopathology also hold promise. Mtb’s adaptation to the human host involves manipulating host cellular mechanisms, and HDT aims to disrupt this manipulation to enhance treatment effectiveness. Our review provides valuable insights for future anti‐TB drug development efforts.